2017
DOI: 10.1542/peds.2016-3148
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for the Treatment of SLC29A3 Mutation Positive PHID Syndrome

Abstract: Pigmentary hypertrichosis and non-autoimmune insulin-dependent diabetes mellitus (PHID) is associated with recessive mutations in , encoding the equilibrative nucleoside transporter hENT3 expressed in mitochondria, causing PHID and H syndromes, familial Rosai-Dorfman disease, and histiocytosis-lymphadenopathy-plus syndrome. Autoinflammation is increasingly recognized in these syndromes. We previously reported a 16-year-old girl with PHID syndrome associated with severe autoinflammation that was recalcitrant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Three cases of HS and one case of pigmentary hypertrichosis and non‐autoimmune insulin‐dependent diabetes mellitus syndrome have been successfully treated with tocilizumab after a failure of azathioprine, ciclosporin, methotrexate, anakinra, and/or TNF‐alpha inhibitors 2,3 . Increased levels of IL‐6 were found in our patient, supporting the use of tocilizumab.…”
Section: Figuresupporting
confidence: 63%
See 1 more Smart Citation
“…Three cases of HS and one case of pigmentary hypertrichosis and non‐autoimmune insulin‐dependent diabetes mellitus syndrome have been successfully treated with tocilizumab after a failure of azathioprine, ciclosporin, methotrexate, anakinra, and/or TNF‐alpha inhibitors 2,3 . Increased levels of IL‐6 were found in our patient, supporting the use of tocilizumab.…”
Section: Figuresupporting
confidence: 63%
“…Treatment options are limited. Four pediatric patients with SLC29A3 mutations treated with tocilizumab (anti‐IL‐6 receptor) have been reported 2,3 . We report the first case of adult HS successfully treated with tocilizumab.…”
Section: Figurementioning
confidence: 96%
“…SLC29A3 encodes a nucleoside transporter which plays a significant role in the cellular uptake of nucleosides and nucleobases. It was previously reported that many diseases were related to RAD51AP1 expression, including autoinflammatory diseases [ 46 ], H syndrome [ 47 ], insulin-dependent diabetes [ 48 ], pigmentary hypertrichosis, autoimmune insulin-dependent diabetes mellitus [ 49 ], and sclerosing bone dysplasias [ 50 ]. Meanwhile, MIMT1 is an MER1 repeat-containing imprinted transcript, which can undergo hypermethylation in the placenta of intrauterine growth-restricted fetuses in cattle [ 51 ], and truncation of exons 3 and 4 of the MIMT1 gene caused intrauterine growth restriction [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options reported in the literature include systemic corticosteroids, methotrexate, cyclosporine, cyclophosphamide, interferon alfa, colchicine, interleukin‐1 receptor antagonists, canakinumab, adalimumab, nonsteroidal anti‐inflammatory drugs, tocilizumab, and radiotherapy, primarily for the inflammatory features of the disorder . Treatment with tocilizumab may show the most promise as partial to complete response has been reported with the use of this drug …”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Treatment with tocilizumab may show the most promise as partial to complete response has been reported with the use of this drug. 10,12 Our patient had been evaluated and followed for many years by many specialists without consideration of H syndrome. However, given the characteristic cutaneous features, he was readily diagnosed when seen in our dermatology clinic.…”
mentioning
confidence: 99%